Coding Learning Approaches for Early Childhood: A Systematic Review - Bayu Widyaswara Suwahyo (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2024)
As digital literacy becomes a core component of early childhood education, there's an increasing urgency to figure out how best to introduce computational thinking and programming to young learners. Despite growing interest, a clear gap remains: we still lack age-appropriate strategies and teaching tools that effectively support coding education at this developmental stage. This study tackles that gap through a systematic review of experimental research, focusing on how different teaching methods, learning media, and children's ages influence their ability to grasp coding concepts in early education settings. Drawing on data from four major academic databases—Scopus (436 articles), ScienceDirect (284), EBSCOhost (107), and Web of Science (86)—the review screened publications from 2020 to 2024. After applying rigorous inclusion and exclusion criteria, 29 relevant experimental studies were selected for in-depth analysis. The findings highlight that tangible learning tools, such as physical coding toys, significantly enhance young children's comprehension. The teaching strategies reviewed fell into three broad categories: plugged-in (digital), unplugged (non-digital), and hybrid. Notably, age plays a critical role in how children engage with and understand coding, especially in instruction-heavy environments. While both plugged and unplugged approaches were beneficial, unplugged methods stood out as particularly effective thanks to their hands-on and developmentally appropriate nature. Overall, this review adds meaningful insights to the field of early coding education and offers practical guidance for educators and policymakers looking to build responsive, age-sensitive curricula that foster digital readiness from an early age.